Upaya Perangkat Desa dalam Memberdayakan Masyarakat di Desa Tengah Padang Kecamatan Talang Empat Kabupaten Bengkulu Tengah - Desi Anggraini; Ilham Adbullah; Parlan Parlan (UNIB Press, Universitas Bengkulu, 2019)
The aim of this research were: (1) to know the empowering society planning program by the village staff (2) to know the activity of empowering society done by the village staff (3) to know the effort of filling the competence aspect on the empowering society activity (4) to know the innovative effort which was done by the village staff in order to increase the quality of empowering society activity. The research method was qualitative method with descriptive approach. The participants of this research were Mr. Jamali as the headman, Mrs. Titing Alfera Roza, S.Pd as the secretary, Ms.Septi Andriani as the head of youth organization and Mrs. Linda Dewi as the one of Tengah padang village members. The data collection technique used non-participant observation, structured interview, and documentation. The data analysis technique used Miles and Huberman analysis mode, which was consist of the data reduction, data presentation, and drawling conclusion. On behalf of examining the validity and reliability of the data, the researcher used triangulation on the source, technique, and time. Based on the analysis, the village staff had done the effort to empower the society in Tengah Padang village, Talang Empat Sub-District, Central Bengkulu Regency such as arranging the empowering society planning program. The planning activities were PKK coaching, sport activity, art activity, religious activity, English and computer course. The village staff did the location and socialization selection, the empowering fund got from ADD. The support factor was the high of society participation, on the other hand the minimum facility was the inhibit factor. In order to fill the competence aspect, the village staff searched the speaker who appropriate with the education background. The innovative effort was planning the new activity such as making the bag from the strap. Then there was the directly checking by the village staff with observing the activity. Key Words: Effort, The Village Staff, Empowering Society